Development of a colloidal gold immunochromatographic strip for the simultaneous detection of porcine epidemic diarrhea virus and transmissible gastroenteritis virus - Zhou, Jinzhu; Wu, Wei; Wang, Dandan; Wang, Wei; Chang, Xinjian; Li, Yunchuan; Li, Jizong; Fan, Baochao; Zhou, Junming; Guo, Rongli; Zhu, Xuejiao; Li, Bin (Frontiers in Microbiology, 2024)
In recent years, porcine diarrhea associated viruses caused disastrous economic losses all over the world. Not only there are similar clinical symptoms including watery diarrhea, dehydration and vomiting, but also there is often co-infection with porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV). For the rapid and on-site preliminary diagnosis on the pig farms, this study aimed to develop a colloidal gold immunochromatography assay (GICA) strip for detection of PEDV and TGEV simultaneously. The GICA kit showed that there were not crossreactivity with other 5 common porcine viruses. With visual observation, the lower limits were approximately 10 4 TCID50/mL and 10 4 TCID50/mL for PEDV and TGEV, respectively. The GICA strip could be stored at 4°C or 25°C for 12 months without affecting its efficacy. To validate the GICA strip, 121 clinical samples were tested. The positive rates of PEDV and TGEV were 42.9% and 9.9%, respectively, and the co-infection rate of two viruses was 5.8% based on the duplex GICA strip. Thus, the established GICA strip is rapid, specifical and stable tool for on-site preliminary diagnosis of PEDV-and TGEV-associated diarrhea.